The role of activation of two different sGC binding sites by NO‐dependent and NO‐independent mechanisms in the regulation of SACs in rat ventricular cardiomyocytes - Andre G. Kamkin; Olga V. Kamkina; Andrey L. Shim; Andrey Bilichenko; Vadim M. Mitrokhin; Viktor E. Kazansky; Tatiana S. Filatova; Denis V. Abramochkin; Mitko I. Mladenov (Physiological Reports, 2022)
Abstract The mechanoelectrical feedback (MEF) mechanism in the heart that plays a significant role in the occurrence of arrhythmias, involves cation flux through cation nonselective stretch‐activated channels (SACs). It is well known that nitric oxide (NO) can act as a regulator of MEF. Here we addressed the possibility of SAC’s regulation along NO‐dependent and NO‐independent pathways, as well as the possibility of S‐nitrosylation of SACs. In freshly isolated rat ventricular cardiomyocytes, using the patch‐clamp method in whole‐cell configuration, inward nonselective stretch‐activated cation current ISAC was recorded through SACs, which occurs during dosed cell stretching. NO donor SNAP, α1‐subunit of sGC activator BAY41‐2272, sGC blocker ODQ, PKG blocker KT5823, PKG activator 8Br‐cGMP, and S‐nitrosylation blocker ascorbic acid, were employed. We concluded that the physiological concentration of NO in the cell is a necessary condition for the functioning of SACs. An increase in NO due to SNAP in an unstretched cell causes the appearance of a Gd3+‐sensitive nonselective cation current, an analog of ISAC, while in a stretched cell it eliminates ISAC. The NO‐independent pathway of sGC activation of α subunit, triggered by BAY41‐2272, is also important for the regulation of SACs. Since S‐nitrosylation inhibitor completely abolishes ISAC, this mechanism occurs. The application of BAY41‐2272 cannot induce ISAC in a nonstretched cell; however, the addition of SNAP on its background activates SACs, rather due to S‐nitrosylation. ODQ eliminates ISAC, but SNAP added on the background of stretch increases ISAC in addition to ODQ. This may be a result of the lack of NO as a result of inhibition of NOS by metabolically modified ODQ. KT5823 reduces PKG activity and reduces SACs phosphorylation, leading to an increase in ISAC. 8Br‐cGMP reduces ISAC by activating PKG and its phosphorylation. These results demonstrate a significant contribution of S‐nitrosylation to the regulation of SACs.